74 days under the Argentine flag: The experiences of occupation during the Falklands/Malvinas War - Alejandro Luis Corbacho (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2018)
The experience of military occupation confronts two groups of people in an asymmetrical relation of power established by the occupiers and suffered by the occupied. Once the occupation ends, this traumatic situation leaves a deep imprint in the memory of the occupied. The occupation of the Falkland/Malvinas Islands by Argentine troops that triggered the South Atlantic War in 1982 lasted 74 days and the cooperation from the islanders was negligible; they resorted to passive resistance, and showed their rejection of the invaders at every possible opportunity and the islanders even helped the British troops by providing intelligence and guidance on the terrain. This paper assesses the experience of the Argentine occupation. How did this small, tightly-knit islander community cope with the traumatic event of an occupation? How did the Argentine military personnel act and react during this period? In short, how did they conduct the occupation? How separated were the cultures of both occupiers and occupied? Until now this story has been told in a fragmentary form, scattered across different sources. This paper intent to put these fragments together and narrates the experience from three sides (the occupiers, the occupied and the liberators). Further analysis centers on the lasting effects of the occupation in the memories of three sides (the Argentineans, the islanders, and the British). The sources are interviews about the experience of the direct participants that were published shortly after the war and written material over the experience already published by both sides. This work shows that the views clashed at two different levels: one, about the interpretation of the rights and claims. How each country tells the story of possession and dispossession of the islands. The second level, considers the cultural characteristics of each group: the two cultures clashed because of differences in language, heritage, political and judicial traditions. Analysis of this case can yield important insights into occupations, particularly the "friendly" type, in which occupiers attempt to win the hearts and minds of the occupied, or, failing that, at least not antagonize them greatly.
Keywords: 330